2002
DOI: 10.1038/nature00941
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of magnesium activation of calcium-activated potassium channels

Abstract: Large-conductance (BK type) Ca(2+)-dependent K(+) channels are essential for modulating muscle contraction and neuronal activities such as synaptic transmission and hearing. BK channels are activated by membrane depolarization and intracellular Ca(2+) and Mg(2+) (refs 6-10). The energy provided by voltage, Ca(2+) and Mg(2+) binding are additive in activating the channel, suggesting that these signals open the activation gate through independent pathways. Here we report a molecular investigation of a Mg(2+)-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
278
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(294 citation statements)
references
References 29 publications
12
278
1
1
Order By: Relevance
“…Other divalent cations, such as Cd 2+ , Mn 2+ , Fe 2+, Co 2+ , and Ni 2+ , also were able to enhance activation and increase the Hill coefficient of channels already activated by Ca 2+ (Oberhauser et al, 1988). Recently, it was discovered that most of these cations are able to activate the BK channel in the absence of Ca 2+ by binding to a low affinity site (Shi and Cui, 2001;Zhang et al, 2001;Shi et al, 2002;Zeng et al, 2005).…”
Section: Sensing Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other divalent cations, such as Cd 2+ , Mn 2+ , Fe 2+, Co 2+ , and Ni 2+ , also were able to enhance activation and increase the Hill coefficient of channels already activated by Ca 2+ (Oberhauser et al, 1988). Recently, it was discovered that most of these cations are able to activate the BK channel in the absence of Ca 2+ by binding to a low affinity site (Shi and Cui, 2001;Zhang et al, 2001;Shi et al, 2002;Zeng et al, 2005).…”
Section: Sensing Elementsmentioning
confidence: 99%
“…These residues that are conserved in mSlo1 and dSlo1 but not in Slo3 were mutated to the corresponding amino acids present in Slo3 with the result that two hot spots were found, E374A and E399N ( Fig. 3C; Shi et al, 2002). Mutation of either of these two residues completely obliterated Mg 2+ -dependent activation.…”
Section: Sensing Elementsmentioning
confidence: 99%
“…Magnesium ions (Mg 2+ ) play an important role in mammalian cell function [1][2][3][4], as an enzymatic cofactor [5], regulator of cellular ion channels [6][7][8] and energy metabolism [9]. Conditions such as Type 2 Diabetes [10][11][12], Alzheimer's [13,14] and cardiovascular disease [15,16] have been linked with magnesium deficiency, however the mechanisms of Mg 2+ regulation in such disease states are poorly understood [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence indicates that intra--cellular Mg 2+ can modulate the activity and selectivity of these channels therefore affecting monovalent cation permeability. While an effect of intracellular Mg 2+ on CRAC channels cannot be completely excluded, a report by Prakriya and Lewis (2002) (Shi et al, 2002). The inhibitory effect of Mg 2+ is not restricted to cell membrane channels.…”
Section: Physiological Role Of Intracellular Mg 2+mentioning
confidence: 99%
“…Recent studies have revealed that these two types of cell death exist following exposure to intense noise and that apoptosis appears extremely rapidly after the noise stress. Apoptosis has been shown to be the primary cell death pathway in the first day following noise exposure (Hu et al, 2002;. Contrary to birds or reptiles, a mammal's auditory hair cells do not regenerate if they are destroyed.…”
Section: Ischemic Processmentioning
confidence: 99%